KEARIFAN LOKAL DALAM PENGELOLAAN SUMBER DAYA PESISIR DAN LAUT Hukum Adat Laot dan Lembaga Panglima Laot di Nanggroe Aceh Darussalam - Puspita, Maya (Fakultas Ilmu Budaya Universitas Diponegoro, 2008)
The fisherman communities of Aceh Nangroe Darussalam has been aware to manage their potential resources, their coast and seas for centuries equipped with local indigenous values tradition and culture, so-called â€žtraditional wisdom.â€Ÿ The traditional wisdom implied in this region includes the authority ground of Panglima Laot, fishing time determination and the system of marine management cooperated with local government. The sanction is also applied as a consequence of its violation. They respect the nature a lot and believe if they â€œtreatâ€ the nature wisely and gently, it will give them something in return. They well manage between the local indigenous values tradition and culture and management of coastal and marine resources in order to maintain the sustainability of the resources. Primarily, after the tsunami, the fishermen society became more cautious and aware to preserve the ocean along with the resources.